2020
DOI: 10.1002/alz.046297
|View full text |Cite
|
Sign up to set email alerts
|

A novel MRI contrast weighted ratio method for measuring myelin in older adults at risk for Alzheimer’s disease

Abstract: Background MRI measures sensitive to myelin integrity such as the T1/T2 weighted ratio method (T1w/T2w; Glasser & Van Essen 2011) have been investigated as potential AD biomarkers. Many cohorts have transitioned to T1 and T2‐weighted Fluid Attenuated Inversion Recovery (FLAIR) acquisitions. Our goal was to validate the T1w/T2FLAIRw method in comparison to the T1w/T2w method in the same cohort. Method 28 cognitively unimpaired (CU, cognitively normal and subjective cognitive decline) and 26 AD‐related cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…First, we selected participants with images containing three structural MRI (sMRI) modalities (T1, T2‐star, and T2‐flair) and matched PET AV45 within 3 months. The three sMRI modalities were chosen for the following reasons: they were the most widely used sequences in clinical AD examinations; Previous literature suggested that they are potential biomarkers for the diagnosis of AD (Fleisher et al, 2011; Price et al, 2020; van Rooden et al, 2015; Xie et al, 2019); Prior evidence also indicates they were significantly associated with cerebral Aβ deposition (Fleisher et al, 2011; Grimmer et al, 2012; van Rooden et al, 2014; Yasuno et al, 2017). Then, a visual inspection was carried out to ensure acceptable image quality.…”
Section: Methodsmentioning
confidence: 99%
“…First, we selected participants with images containing three structural MRI (sMRI) modalities (T1, T2‐star, and T2‐flair) and matched PET AV45 within 3 months. The three sMRI modalities were chosen for the following reasons: they were the most widely used sequences in clinical AD examinations; Previous literature suggested that they are potential biomarkers for the diagnosis of AD (Fleisher et al, 2011; Price et al, 2020; van Rooden et al, 2015; Xie et al, 2019); Prior evidence also indicates they were significantly associated with cerebral Aβ deposition (Fleisher et al, 2011; Grimmer et al, 2012; van Rooden et al, 2014; Yasuno et al, 2017). Then, a visual inspection was carried out to ensure acceptable image quality.…”
Section: Methodsmentioning
confidence: 99%
“…In the human brain, the SFO can either be an isolated fasciculus or a branch of the superior longitudinal fasciculus (Bao et al., 2017). It plays a major role in speech and language, as well as the top‐down modulation of visual processing and spatial aspects of cognitive processing (Bar et al., 2006; Schmahmann et al., 2007), and was found to be associated with cognitive decline in the aging population (Price et al., 2020). Negative direct/total effects are mainly observed in the lateral ventricles.…”
Section: The Alzheimer's Disease Neuroimaging Initiative Studymentioning
confidence: 99%
“…In the human brain, the SFO can either be an isolated fasciculus or a branch of the superior longitudinal fasciculus (Bao et al, 2017). It plays a major role in speech and language, as well as the top-down modulation of visual processing and spatial aspects of cognitive processing (Bar et al, 2006;Schmahmann et al, 2007), and was found to be associated with cognitive decline in the aging population (Price et al, 2020). Negative direct/total effects are mainly observed in the lateral ventricles.…”
Section: The Alzheimer's Disease Neuroimaging Initiative Studymentioning
confidence: 99%